STUDY EFFECT OF COATING ANGEL ON PARAMETERS OF ROCK STRENGTH ON THE LAYERD MATERIAL - HANDRIATNO KABAU (NIM : 12112049), HENDRA
Discontinuous rock mass are often found in mining activities. Rock mass is usually formed from many rock types, separated by several stocks that can be filled by fill material and have different relative strengths for each constituent rock. The rock mass strength is strongly influenced by the frequency of the discontinuous fields formed. This study use samples made of sand, cement and water with different cement-sand compositions. For material A is a material with 1:1 cementsand composition, and material B is a material with 1:3 cement-sand composition. The samples were made with cylindrical and beam samples, for cylindrical samples having a high dimension of Ã‚Â± 10cm with a diameter of Ã‚Â± 5cm ( total of 12 pieces) with homogen material of each sample and a length beam sample Ã‚Â± 12cm, width Ã‚Â± 12cm and height Ã‚Â± 24cm ( total of 12 pieces) with AB-A and B-A-B (6 pieces each) that have variations of 90◦, 80◦, 70◦, 60◦, 50◦ and 40 sudut coating angles. Several laboratory scale tests were performed to obtain data related to the equivalent young modulus such as: rock physical properties, compressive strength values, axial deformations and shear strength. In this study for beam samples is a sample consisting of two materials ie material A and material B which is combined without using adhesive then the sample of the beam is done by uniaxial compressive strength to see the value of compressive strength and modulus young.